Fatty acids and contaminants in edible marine gastropods from Patagonia - Bigatti, Gregorio (2017)
Edible marine gastropods are consumed in northern Patagonia without regulations or knowledge of nutritional composition and food quality. We determined total lipids (TL), fatty acid (FA), paralytic shellfish poison (PSP) and metal contamination in six edible marine gastropods: Buccinanops globulosus, B. cochlidium, Trophon geversianus, Odontocymbiola magellanica, Tegula patagonica and Nacella magellanica. TL was lowest in the foot (0.29–0.56%) and maximum in organs (1.43–3.2%), presenting less TL than other edible species around the world. Saturated FA were similar to other consumed marine gastropods worldwide and dominant in all species studied (33.26–48.19%), while monounsaturated FA reached about 30% only in 2 species, but did not exceed 18% in the other species. Polyunsaturated FA reached up to 23.77%, but generally did not exceed 14%. Highly unsaturated FA (AA, EPA and DHA), reached about 27%. The dominant FA was palmitic acid (0.217 to 2.43 µg mg−1).Differences in FA could be related to the different alimentation of the species. Limit of PSP consumption was exceeded in a few months only for two species. Lead was not detectable (<4 µg g−1) while cadmium ranged from 0.07 to 15.32 µg g−1. Our results can be useful to ensure the safety food of these resources, which are being consumed and exported in low quantities in Argentina, but may be commercialized massively in the near future. Monitoring these and other food resources is essential and should be performed in any established fishery of the species reported here to guarantee the safety human consumption.